Design Broad Bandwidth Microwave Bandpass Filter Of 10 Ghz Operating Frequency Using HFSS - Jasim, S. E.; Mohamad Ashry, Jusoh (2017)
Microwave bandpass filter is the essential part in microwave circuits and wireless communication systems. This paper presents a new designing and simulation of broad bandwidth,low losses microwave bandpass filter operating at 10 GHz frequency using return loss method. The designing and simulation of the circuit has been carried out using Computer Aid Design (CAD) Ansoft HFSS software purchase from Ansys. The microwave filter circuit has designed with a parallel coupled line having a small dimension (10 × 10 mm2) of LaAlO3 substrate. The microwave circuit showed a high return loss -20 dB, broad bandwidth of 1.5 GHz, and operating frequency at 10 GHz. The results indicate the filter design and simulation using HFSS is reliable and have the opportunity to transfer from lab potential experiments to industry.